VD_FINDINFO 2/2016 vom 11. Januar 2016 - VD Tribunal cantonal (2016)
RÉCUSATION, ADMISSION DE LA DEMANDE | 6 al. 1 let. a ROTC, 47 al. 1 let. a CPC (CH), 47 CPC (CH), 48 CPC (CH), 8a al. 3 CDPJ, 8b al. 4 CDPJ